Precise residual stress profile in ion-exchanged silicate glass by modified contour method. Issue 7 (July 2021) - Sun, Huan; Dugnani, Roberto
Highlights: A modified contour method was used to measure stresses in ion-exchanged glass. The method proposes using weight functions to account for inhomogeneous properties. Residual stresses were compared to optical waveguide predictions. Optical waveguide appears to overestimate the surface residual stress by 10–30 %. Abstract: In this work, the contour method is modified and used to precisely estimate the residual stress profiles in ion-exchanged aluminosilicate glasses, including the effects of non-homogeneous material properties. The method requires the precise measurements of the fracture surface's topography and exploits fractographic features to mate and accurately determine the out-of-plane deformation after fracture. Residual stresses are computed from the out-of-plane deformation through a weight function approach rather than by numerical methods, as weight functions can easily account for concentration-dependent material properties. The stress profiles in aluminosilicate glass with three different molten salt soaking times were calculated and compared with the approximate profiles measured by optical waveguide. It was found that the optical waveguide's estimations under-predicts the surface stress by as much as 10–30 %, likely due to the assumption that the stress optic coefficient is unaffected by the K + ↔ N a + exchange.